The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.bjc.6603444
|View full text |Cite
|
Sign up to set email alerts
|

Activated c-SRC in ductal carcinoma in situ correlates with high tumour grade, high proliferation and HER2 positivity

Abstract: Overexpression and/or activity of c-Src non-receptor tyrosine kinase is associated with progression of several human epithelial cancers including breast cancer. c-Src activity in 'pure' ductal carcinoma in situ (DCIS) was measured to assess whether this predicts recurrence and/or correlates with HER2 expression and other clinical parameters. Activated c-Src levels were evaluated in DCIS biopsies from 129 women, with median follow-up at 60 months. High levels of activated c-Src correlated with HER2 positivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 24 publications
4
62
1
Order By: Relevance
“…Madan et al (2006) subsequently showed that c-Src activation did not correlate with the development of invasive tumour properties but correlated with malignant transformation. In ductal carcinoma in situ, activated c-Src was found to correlate with high tumour grade, high proliferation and HER 2 positivity, suggesting that high c-Src activity may identify a subset of DCIS at risk of disease progression to invasive carcinoma (Wilson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Madan et al (2006) subsequently showed that c-Src activation did not correlate with the development of invasive tumour properties but correlated with malignant transformation. In ductal carcinoma in situ, activated c-Src was found to correlate with high tumour grade, high proliferation and HER 2 positivity, suggesting that high c-Src activity may identify a subset of DCIS at risk of disease progression to invasive carcinoma (Wilson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has recently been reported that expression of activated Src is associated with a reduced recurrencefree survival in ductal carcinoma in situ [15]. Steroidinduced cellular responses involve activation of Src and, although the molecular pathways involved in these responses have yet to be fully defined, can involve growth factor receptor signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Src kinases are potently transforming and tumorigenic when constitutively activated, and their activation is seen in many human tumor types, including breast cancers with or without HER2 overexpression (Ottenhoff-Kalff et al, 1992; Belsches-Jablonski et al, 2001; Reissig et al, 2001). An association between src activation and HER2 overexpression has been reported in pre-invasive carcinomas of the breast (Wilson et al, 2006). Mammary tumors that arise in MMTV-neu transgenic mice have activation of c-src and c-yes (Muthuswamy et al, 1994;Muthuswamy and Muller, 1995a).…”
Section: Role Of Src Kinasesmentioning
confidence: 99%